A computational method based on hybrid of block-pulse functions and Taylor series for solving two-dimensional nonlinear integral equations - Farshid Mirzaee (Alexandria Engineering Journal, 2014)
In this paper, a new reliable technique, which is based on hybrid functions approximation, is introduced for the approximate solutions of two-dimensional nonlinear Fredholm and Volterra integral equations. The properties of block-pulse functions together with the Taylor series are used to reduce the problem to the solution of nonlinear algebraic equations. Illustrative examples have been discussed to demonstrate the validity and applicability of the technique and the results show reliability and efficiency of the proposed method.